2008
DOI: 10.1002/jrs.2052
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the vibrational pattern of ring structures in the Raman spectra of vitreous silica

Abstract: Raman scattering spectra of silica glass models were studied by means of molecular dynamics computer simulation. The study principally aimed at the inspection of the assignment of the defect bands of the Raman spectra of a-SiO2 proposed by Galeener and co-workers (Galeener FL, Barrio RA, Martinez E, Elliott RJ. Phys. Rev. Lett. 1984; 53: 2429). The results of the study have shown that the D2 peak at 606 cm-1 can probably be related to the presence of three-membered rings in a-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…[7][8][9][10][11][12][13] Information about vibrations is available from the common techniques of IR and Raman spectroscopy, however, the visibility of modes is strongly dependent on complicated cross sections. An alternative experimental method is inelastic neutron scattering ͑INS͒, in which vibrations are probed by energy exchanges with thermal neutrons.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Information about vibrations is available from the common techniques of IR and Raman spectroscopy, however, the visibility of modes is strongly dependent on complicated cross sections. An alternative experimental method is inelastic neutron scattering ͑INS͒, in which vibrations are probed by energy exchanges with thermal neutrons.…”
mentioning
confidence: 99%
“…Raman scattering spectra of silica glass models were studied by To et al [177] by molecular dynamics computer simulation. This study aimed to assign the defect bands of the experimentally observed Raman spectra of a-SiO 2 .…”
Section: Glasses Ceramics and Disordered Materialsmentioning
confidence: 99%
“…[87,88] A recent study summarizes the noncompletely converging results of previous modeling analyses and suggests an interpretation suitable for a critical use of the experimental data for the structural characterization of the materials. [89] The main drawback of many previous studies was that the used classical approaches did not dispose on a reliable model for the calculation to the Raman intensity (Zotov et al [78] tried to calculate the Raman spectra of Na 2 Si 4 O 9 and SiO 2 glasses, but as the authors neglected the derivative of the transversal polarizability, they were not able to calculate intensities of the defect bands), while first-principles calculations, potentially capable of providing the most reliable results, were constrained to use small structural models, which could not yield a representative distribution of ring structures and thus led to large uncertainties on the calculated Raman intensities. The work in ref.…”
Section: Aluminosilicatesmentioning
confidence: 99%
“…The work in ref. [89] used a silica glass model of 1536 atoms giving rise to a reasonable statistics of the rings as well as to a reliable calculation of the Raman spectrum with the parameters previously presented.…”
Section: Aluminosilicatesmentioning
confidence: 99%
See 1 more Smart Citation